Engineering undergraduates’ perspectives of effective platforms forpresentation in English - Palpanadan, Sarala @ Thulasi; Kadir@Shahar, Hazila; Md Ngadiran, Nurizah (International Journal of Innovations in Management, Engineering and Science (IJIMES), 2020)
A good presentation skill has become a crucial ability for engineering undergraduates to master in order to perform well in academic domains as well as at work place. However, it has been noticed that engineering graduates lack in technical presentation skills especially in English due to which they are unable to find suitable jobs in the job market. Thus, this paper exploresthe perspectives of engineering undergraduates with regard to effective presentation skills that they prefer and find useful.This study investigated the perspectives of engineering undergraduates at a technical university in Malaysia. This paper presents the descriptive data that highlights the technology-based platform that engineering students preferred in conducting presentation. The paper also revealed the factors that were considered important for the engineering students in preparing effective slide presentation. A quantitative method was employed where a survey was conducted using a self-developed questionnaire using Google Form and distributed among the engineering students via WhatsApp. The data were collected and analyzed in relation to the research objectives by obtaining the percentage and tabulating according to the ranking identified.The results revealed that thepreferred technology-based platforms employed in presentation slide PowerPoint, Prezi and PowToon that have the useful characteristics for their perusals. The findings also highlighted the factors enhancing their understanding of the presentation slides such as the usage of pictures and animations by avoiding too wordy and information-cramped slides.The finding of this study can be utilized as recommendations to be included in the engineering curriculum to ensure that the engineering graduates become successfulprofessional presentersat the workplace.